Upaya konselor dalam mengatasi permasalahan anak jalanan - Bertha Mazela Febriani; Lidya Puspita; Evan Pratama (Indonesian Counselor Association (IKI), 2017)
Street Children Are Children whose Daily Life Is On The Road To Make A Living. The existence of a child on the street, something very dilemmatic. Lust Seeks Money To Get The Money That Makes It Survive, The Presence Of Children On The Street Often Disrupts Public Order And Their Rights As Children For Affection, Education And Livelihoods That Are Worth Not Separated Again Can Ruin Their Life In The Future. They Are Social Groups That Are Very Vulnerable From Physical Children, Emotions, Or Other Social Violence. Street Children, Like Children, Born With Talents And Interests, Nothing And Develop Because Of The State Of Experiences. And Have Hope or Ideas That Are So Great for Himself.